Perbandingan Perlindungan Konsumen Aplikasi Open Banking di Indonesia dan Malaysia - Gessica Aulya Rahmy Dias; Purwono Sungkowo Raharjo; Sapto Hermawan (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to find out how the relevant regulations and governments in Indonesia and Malaysia work to protect consumers of open banking applications. The type of research used is normative legal research, prescriptive and applied in nature using deductive syllogism reasoning method analysis. The approach used is a statutory approach (statue approach) and comparative approach with primary legal materials including various types of laws and regulations regarding consumer protection in Indonesia and Malaysia, as well as secondary legal materials including books, journal articles, and official documents. The results show that there are differences in consumer protection in Indonesia and Malaysia which are analyzed through 4 (four) indicators, namely consumer protection regulations, consumer protection law enforcement agencies, consumer dispute resolution mechanisms, and open banking supervisory institutions.